Electrosurgery in urology: recent advances. (September 2011) - Tremp, Mathias; Hefermehl, Lukas; Largo, Remo; Knönagel, Hartmut; Sulser, Tullio; Eberli, Daniel
Inadequate hemostasis is one of the most important causes of morbidity and mortality following urological surgery. Despite the long-term usage of coagulation, there is an ongoing development of new devices, including bipolar transurethral resection of the prostate or new vessel-sealing devices. A thorough understanding of the advantages and disadvantages of these new instruments can improve the operative experience for both the urologist and patient. The optimal coagulation system should be small, efficient, easy to handle and with low heat spread. In this article, we analyze different electrothermal coagulation systems and modern tissue-sealing devices in urological applications with the aim to substantiate the advantages and disadvantages of each technique in terms of efficacy and safety.